Ewolucja ideologiczna Partii Konserwatywnej w Wielkiej Brytanii w latach 2005–2012 - Dulęba, Łukasz (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2014)
The ideology of Conservative Party from its own beginning remains full of contradictions. On the one hand, the governments of Benjamin Disraeli and Harold Macmillan realized the conceptions of state intervention, but on the other hand during Margaret Thatcher’s leadership Conservative Party made a strong turn to free market policies based on privatization of various sectors of British economy, and reduce the redistributive tools. After the leadership contest, won by David Cameron, appeared a possibility of rejection of neoliberal ideology in favor of building a civil society based on egalitarian values. However, despite arguments for a change, after coming to power Conservatives returned to criticized policies. An attempt to build communitarian perspective was challenged by the neoliberal solutions.
Ideological of Conserwative Party in Great Britian 2005–2012